MASLAHAH AL-MURSALAH DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA (Perspektf NU dan Ulamā Mazdhāhib AL-Arbā’ah ) - Yusuf hadziq; Kawakib Kawakib (Al-Maslahah : Jurnal Ilmu Syariah, 2020)
Islamic Shari’ah is very concerned about the realization of welfare and general benefit in the life of the nation and state. Public benefit accommodates the interests of all parties regardless of faith, class, skin color and does not contradict with Islamic law (Qur'an, hadith, ijmâ and qiyas). Maslahah 'âmmah is the benefit that leads to the principle of justice, freedom and human equality in front of law. Maslahah 'âmmah must have the principle of syûra (deliberation), Maslahah 'âmmah is determined, must go through representative institutions as the aspirations of the people, as well as for their interests, which is decided in the Law on people's representative institutions (majlis istisyâri) which the government must guide as honest executors and consequently, and there must be positive support and control over representative institutions as formulators (legislative), as law enforcing judiciary (judiciary). The implication of the difference in the concept of maslahah 'âmmah will increase the breadth of the concept or make it easier to limit and seek decisions of public interest (maslahah 'âmmah), in accordance with the times that are increasingly rotating in the midst of life. Because in essence, all of this comes down to one goal, namely the realization of benefit 'âmmah (universal goodness). Ijtihad produced by Nahdlatul Ulama, in realizing maslahah 'ammah and rejecting danger, is elastic in accordance with the times and conditions. Because the two concepts of NU and madzhâhib al-Arbâ'ah can complement or strengthen both of them, and the decisions that NU come up are stronger. Because NU in formulating maslahah 'âmmah only adds or completes it. For example, decisions must be based on the provisions of syûra (voice of government and people).